Size Reduction and Gain Enhancement of a Microstrip Antenna using Partially Defected Ground Structure and Circular/Cross Slots - Nada N. Tawfeeq (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Microwave engineers have been known to designedly created defects in the shape of carved out patterns on the ground plane of microstrip circuits and transmission lines for a long time, although their implementations to the antennas are comparatively new. The term Defected Ground Structure (DGS), precisely means a single or finite number of defects. At the beginning, DGS was employed underneath printed feed lines to suppress higher harmonics. Then DGS was directly integrated with antennas to improve the radiation characteristics, gain and to suppress mutual coupling between adjacent elements. Since then, the DGS techniques have been explored extensively and have led to many possible applications in the communication industry. The objective of this paper is to design and investigate microstrip patch antenna that operates at 2.4 GHz for Wireless Local Area Network WLAN IEEE 802.11b/g/n, ,Zigbee, Wireless HART, Bluetooth and several proprietary technologies that operate in the 2.4 GHz band. The design of the proposed antenna involves using partially Defected Ground Structure and circular/cross slots and compare it to the traditional microstrip patch antenna.  The results show improvement in both the gain of 3.45 dB and the S11 response of -22.3 dB along with reduction in the overall dimensions of the antenna. As a conclusion, the performance of the antenna has been improved through the incorporation with the DGS and slots structures regarding the S11 response and the gain. The proposed antenna become more compact. Finally, the radiation pattern of proposed antenna has remained directional in spite of adding slots on the ground plane.